Achieving Inclusive Growth in the Asia Pacific - Adam Triggs; Shujiro Urata (Australian National University Press, 2020)
The world's developed economies are experiencing a sharp backlash against globalisation, and it appears to be contagious. Will Asia catch it next? Asia has seen spectacular growth in recent decades. It has benefited substantially from global trade, finance, openness and the rules-based international order. But much of the growth Asia has enjoyed has not been shared. It has not been inclusive growth. Inequality in Asia is among the highest in the world. The richest man in Vietnam now earns more in a single day than the poorest person does in a decade. Asia has far to go in making its societies more inclusive to women, ethnic minorities and the LGBT community. How can Asia reduce inequality? What are the forces that determine whether growth in the Asia Pacific is inclusive or not? And what can be done to make Asia's growth more inclusive in the future? This book brings together the region's leading thinkers to explore how to change Asia's trajectory, before it is too late. The Pacific Trade and Development (PAFTAD) conference series has been at the forefront of analysing challenges facing the economies of East Asia and the Pacific since its first meeting in Tokyo in January 1968
Keywords: 330; Asia Pacific; globalisation; inequality; inclusivity; economic growth; economic inequality; Inklusives Wachstum; Soziale Ungleichheit; Chancengleichheit; Einkommensverteilung; Generationengerechtigkeit; Gleichberechtigung; Asiatisch-pazifischer Raum